Cyber–Physical–Social Security of High-DER-Penetrated Smart Grids: Threats, Countermeasures, and Challenges - Qiuyu Lu; Jun’e Li; Zhao Peng; Ming Ni (IET Information Security)
With the trend of large-scale renewable distributed energy sources (DERs) penetrating into the smart grids (SGs), the SGs entail heavy reliance on information and communication technologies (ICT) and increasing impact of social behaviors on system operation and management. The SGs can be viewed as cyber–physical–social systems (CPSSs). However, the deep coupling of cyber, physical, and social spaces leads the SGs to be more complex and openness, and thus, a higher risk of exposure to various threats. To study the threats, countermeasures, and challenges of the high-DER-penetrated SGs from a cyber–physical–social perspective, the key features of the SGs on devices, networks, and applications are first analyzed. On this basis, the threats faced by the SGs due to the widespread deployment of terminal devices, open network environments, and the increasing importance of social behaviors are analyzed. Subsequently, the limitations of the deployed security measures in current power systems are discussed, and an overview of the state-of-art countermeasures for the SGs security faced by the threats is organized in three stages: prevention, detection, and mitigation. Finally, the research challenges, key gaps, and future directions for security enhancement of the SGs are also discussed.